Production Factors Efficiency Of Potato Farming In Tosari Village - Titik Wahyuningsih; Agnes Quartina Pudjiastuti; Sumarno Sumarno (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Potatoes (Solanum tuberosum L.), one of seven horticultural products targeted to be developed in 2015 by Directorate General of Horticulture. Pasuruan Regency was be able to produce potatoes up to 50% of the total potato production in East Java. Although potatoes cultivation in the Tosari District is relatively large, potatoes productivity is still a problem for the farmers. This study was aimed at analyzing the factors of production that had a dominant influence on potato production and its technical efficiency in the Tosari Village, Tosari District, Pasuruan Regency. Sample was determined by simple random sampling and amounted to 30 potato farmers. Data were analyzed with multiple linear regression models. Analysis revealed that the significant factors affecting potato production in Tosari Village were urea, SP36, ZA and manure. Application of urea, ZA and manure in potato farming in Tosari Village had not been efficient, so it can be added. Meanwhile, SP36 fertilizer was still applied inefficiently, so it must be reduced..